Factors influencing postoperative recurrence of Crohn's disease in childhood. Issue 5 (May 1991) - Griffiths, A M; Wesson, D E; Shandling, B; Corey, M; Sherman, P M
Abstract : We have reviewed the outcome of all patients undergoing their first intestinal resection for Crohn's disease at this hospital between 1970 and 1987. Recurrence rates, defined by recurrent intestinal symptoms and radiological confirmation of mucosal disease, were calculated using survival analysis. Age, sex, anatomical location of disease, indication for surgery, preoperative duration of symptomatic disease, use of preoperative bowel rest, and pathological features of the resected bowel were analysed individually and jointly as potential risk factors influencing postoperative recurrence of disease. Eighty two patients (age, mean (SD) 14.8 (2.5) years) underwent intestinal resection and were followed postoperatively for a minimum of one year (mean 5.3 (3.3) years). Anatomical location of disease, indication for surgery, and preoperative duration of symptomatic disease were the only factors that significantly influenced the duration of the recurrence free interval. Patients with diffuse ileocolonic inflammation experienced earlier recurrence (50% at one year) than children with predominantly small bowel disease (50% recurrence at five years, p less than 0.0001). Failure of medical therapy independent of disease location as the sole indication for surgery was associated with an earlier relapse than when surgery was performed for a specific intestinal complication such as abscess or obstruction (p less than 0.003). Patients undergoing resection within one year of onset of symptoms experienced delayed recrudescence of active disease (30% recurrence by eight years) compared with patients whose preoperative duration of symptomatic disease was longer (50% recurrence by four years when preoperative duration of disease was one to four years and 50% by three years when disease had been present greater than four years preoperatively, p = 0.03). The mean height velocity of patients with growth potential increased from 2.4 (2.3) cm per year preoperatively to 8.1 (3.4) cm per year in the first postoperative year (p=0.0001). These results support an early approach to surgery in the management of ileal Crohn's disease with or without caecal or right colonic involvement, especially when complicated by persistent growth failure. The higher recurrence rates in more diffuse ileocolonic disease emphasise the need for alternative treatment strategies in these children.